2022
DOI: 10.1155/2022/5118553
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Multiple Extraction Solvents on Antioxidant, Cytotoxic, and Phytotoxic Potential of Taraxacum officinale (L.) Weber ex F.H. Wigg. from Poonch Valley, Azad Kashmir, Pakistan

Abstract: Background. Different parts of Taraxacum officinale (L.) were used in traditional medicine in various parts of the world for the treatment of health problems, and they possess significant biological activities. The present study aimed to estimate phytochemical and biological activities of T. officinale using different extraction solvents. Methods. Methanolic, acetone, and n-hexane extracts of selected species were prepared, and ten secondary metabolites were examined using standard protocols. The antioxidant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Previous studies demonstrated a TPC of 40.51 mg GAE/g for comfrey root [6], while angelica root and burdock root TPC values were similar to those demonstrated previously by the other authors [7,8]. The literature reported a higher TPC value for dandelion root (178.273 mg GAE/g) [9], while the lowest concentration of polyphenols for liquorice root (6.18 mg GAE/g) [10] and marshmallow root (4.53 mg GAE/g) [11]. The Egyptian ethanolic extract of liquorice was characterized by almost two times higher TPC value than in our study, while the water extract of this same herb had a comparable TPC [12].…”
Section: Total Phenolic Contentsupporting
confidence: 84%
“…Previous studies demonstrated a TPC of 40.51 mg GAE/g for comfrey root [6], while angelica root and burdock root TPC values were similar to those demonstrated previously by the other authors [7,8]. The literature reported a higher TPC value for dandelion root (178.273 mg GAE/g) [9], while the lowest concentration of polyphenols for liquorice root (6.18 mg GAE/g) [10] and marshmallow root (4.53 mg GAE/g) [11]. The Egyptian ethanolic extract of liquorice was characterized by almost two times higher TPC value than in our study, while the water extract of this same herb had a comparable TPC [12].…”
Section: Total Phenolic Contentsupporting
confidence: 84%
“…The chosen solvent, ethyl alcohol, is one that people can readily use, avoiding options like acetone or methanol, which might produce better results in extraction yield [21,22] but are impractical and toxic for everyday use. Additionally, we opted for lyophilization as it represents the industrial processing method and provides better storage capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the changes in the amounts of phytochemicals in the methanol extract of A. gymnolobus and the applied IC 50 doses of the extracts was examined by Pearson correlation analysis using GraphPad Prism 9 software. The heat map was prepared bidirectionally in order to observe the variability between the changes in the amounts of phytochemicals and the IC 50 doses [ 85 , 86 ].…”
Section: Methodsmentioning
confidence: 99%